Estimation of activation energy of mechanical modifical of steel ШХ15 in fuel PT and aviation oil AMГ-10 - Богданович, O.I.; Пузік, С.О. (Proceedings of National Aviation University (archive), 2005)
Estimation method of activation energy of the second stage of triboreaction of mechanical-chemical modification Em has been presented. Results of method application illustrate on preliminary conducted tribo-kinetic tested of steel ШХ15 in aviation fuel PT and aviation oil AMГ-10.